Investigating The Influence of The Project Based Learning Model on Students Creative Thinking During Digestive System Learning - Dwi sekar , Andini; Kartika Manalu; Adlini, Miza Nina (Universitas Tidar, 2024)
This research investigates the effect of the Project Based Learning (PjBL) model on students' creative thinking during the digestive system learning at SMAS Brigjend Katamso II. This type of research is a quasi-experiment with a non-equivalent control group design. The population of this study was all XI students at SMAS Brigjend Katamso II, which consisted of 4 classes with a total of 135 students. The research sample using the Cluster Random Sampling technique consisted of two classes: Science 2 with 34 students as the experimental class and Science 3 with 34 students as the control class. The research instrument used was a description test consisting of 4 questions to measure students' creative thinking abilities. This research hypothesis was carried out using the T-test with normal and homogeneous conditions. The results of the post-test analysis of the T test obtained tcount 4.34 and ttable 1.69, thus showing the hypothesis test results that tcount > ttable where Ha was accepted and Ho was rejected. So, there is the influence of the project based learning model on the ability to think creatively about the digestive system material for class XI SMA/MA students.